A Comparative Study of Various Mobility Speeds of Nodes on the Performance of LANMAR in Mobile Ad hoc Network - Dumala, Anveshini; Setty, S. Pallam (International Journal of Computer Sciences and Engineering, 2018)
Mobile Ad hoc Network is a wireless network that is formed for a temporary purpose. Unlike wired network, there is no centralized control over the network. So, all the devices act as both node and router and have the property of moving that leads to the dynamic change in the in the network structure. At any instance of time, there is a change in network size and speed. The moving speed of a node affects the frequency of topological changes in the networks, which in return influences the ability of routing the data packets and maintaining steady routes. These two properties have a noticeable impact on the performance of MANET. The study of effect of one of the most important parameters i.e. network size on the performance of MANET is studied while implementing LANMAR routing protocol.